Manual of industrial microbiology and biotechnology - Baltz, Richard H.; Davies, Julian E.; Demain, A. L. 1927- (Reference Manual, ASM Press., 2010)
The third edition reviews the newest techniques, approaches, and options in the use of microorganisms and other cell culture systems for the manufacture of pharmaceuticals, industrial enzymes and proteins, foods and beverages, fuels and fine chemicals, and other products. Readers will find a rich array of methods and discussions of productive microbial processes, with means for improving the organism, the process, and the product.